Why is party-based autocracy more durable? Examining the role of elite institutions and mass organization. Issue 6 (18th August 2022) - Reuter, Ora John
ABSTRACT: A number of studies show that autocracies with ruling parties are more long-lived than those without. Much of the literature attributes this to party institutionalization at the elite- level, which is said to reduce elite schisms. Others point to the ability of grassroots party organizations to mobilize mass support. There is very little empirical research that examines these different mechanisms. This paper fills that gap using new data from the V-Party database, which provides detailed expert-coded information on the attributes of all autocratic ruling par- ties between 1970 and 2019. I find that both mass-based organization (e.g. well-developed networks of local branches and strong ties to social organizations) and elite-level institutionalization (e.g. depersonalized, collective control over candidate nominations) are associated with regime longevity, but the findings for mass organization are stronger and more robust. The findings suggest that mass organization is one of the main factors that makes party-based autocracy so durable.